Cost of managing atonic postpartum haemorrhage with uterine balloon tamponade devices in public health settings of Maharashtra, India: an economic microcosting study - Siddesh Sitaram Shetty; Kusum Venkobrao Moray; Himanshu Chaurasia; Beena Nitin Joshi (BMJ Open)
Objective Postpartum haemorrhage (PPH) is the worldwide leading cause of preventable maternal mortality. India offers free treatment for pregnancy and related complications in its public health facilities. Management with uterine balloon tamponade (UBT) is recommended for refractory atonic PPH cases. As part of health technology assessment to determine the most cost-effective UBT device, this study estimated costs of atonic PPH management with condom-UBT, Every Second Matters (ESM) UBT and Bakri balloon UBT in public health system of Maharashtra, India.Design Health system cost was estimated using primary economic microcosting, data from Health Management Information System and published literature for event probabilities.Settings Four public health facilities from the state of Maharashtra, India representing primary, secondary and tertiary level care were chosen for primary costing.Outcome measures Unit, package and annual cost of atonic PPH management with three UBT devices were measured. This included cost of medical treatment, UBT intervention and PPH related surgeries undertaken in public health system of Maharashtra for year 2017–2018.Results Medical management of atonic PPH cost the health system US$37 (95% CI 29 to 45) per case, increasing to US$44 (95% CI 36 to 53) with condom-UBT and surgical interventions for uncontrolled cases. Similar cost was estimated for ESM-UBT. Bakri-UBT reported a higher cost of US$59 (95% CI 46 to 73) per case. Overall annual cost of managing 27 915 atonic PPH cases with condom-UBT intervention in Maharashtra was US$1 226 610 (95% CI 870 250 to 1 581 596).Conclusions Atonic PPH management in public health facilities of Maharashtra with condom-UBT, ESM-UBT or Bakri-UBT accounts to 3.8%, 3.8% or 5.2% of the state’s annual spending on reproductive and child health services. These findings can guide policy-makers to include PPH complication management in publicly financed health schemes. Economic evaluation studies can use this evidence to determine cost effectiveness of UBT in Indian settings.